Analysis of Distribution and Season of Crab (Portunus pelagicus) in Indonesia Waters - Dimas Jaya Subakti; Ahmad Shofy Mubarak; Annur Ahadi Abdillah (Universitas Islam Lamongan, 2025)
Blue swimming crab (BSC) (Portunus pelagicus) is an Indonesian export commodity for America. The distribution of BSC can be found in the seas of Java, Madura, Sumatra, Bangka Belitung, Kalimantan and Sulawesi. Differences in BSC habitat conditions and climatic conditions in various Indonesian marine locations influence the distribution and abundance of BSC in each location. Information on the distribution and seasonality of BSC in Indonesian seas is still limited. Analysis of the distribution and season of BSC in Indonesian seas based on a study of catch numbers for 2022-2023 PT Kelola Mina Laut. The highest number of catches was in the Madura, West Java and East Java regions, with the lowest number of catches in the Sulawesi and Bangka Belitung regions. The highest total catch occurred in quarter 2 (April-June) and the lowest total catch occurred in quarter 3 (July-September). This research data can be a basis for developing and exploring the potential of BSC in several Indonesian marine locations, but further analysis needs to be carried out regarding other factors that can influence the distribution and season as well as the catch of BSC fishermen in Indonesian seas.